Fiber-reinforced composites in endodontic practice: a review - Mudunuri, Sowmya; Madhu Varma, K; Kalyan Satish, R; Sita Rama Kumar , Manthena; Sai Dinesh, Jetty; Anil Kumar, Pulidindi (International Journal of Dental Materials, 2020)
Fiber-reinforced composites (FRCs) are a group of non-metallic biomaterials characterized by good mechanical properties, such as high fatigue resistance and fracture toughness growing in popularity in several dental applications. FRCs are a combination of two materials: the reinforcing phase in the form of fibers, which are embedded into the other material, called the matrix phase. Factors influencing the properties of FRCs include fibre properties versus polymer matrix properties, impregnation of fibres in the resin, adhesion of fibres to the polymer matrix, quantity and direction of fibres, and location of the fibre-rich phase in construction. The most commonly used applications of FRCs are in removable dentures, minimally invasive fixed dental prostheses, periodontal splints, root canal posts, and orthodontic retainers. This article discusses in detail the applications of FRCs in endodontics, including root canal posts, reinforcement of restorative composites in restorations and core build-ups and splinting of teeth in dental trauma.